Position Affects Performance in Multiple-Object Tracking in Rugby Union Players - Andrés Martín; Andrés Martín; Ana M. Sfer; Marcela A. D'Urso Villar; José F. Barraza; José F. Barraza (Frontiers in Psychology, 2017)
We report an experiment that examines the performance of rugby union players and a control group composed of graduate student with no sport experience, in a multiple-object tracking task. It compares the ability of 86 high level rugby union players grouped as Backs and Forwards and the control group, to track a subset of randomly moving targets amongst the same number of distractors. Several difficulties were included in the experimental design in order to evaluate possible interactions between the relevant variables. Results show that the performance of the Backs is better than that of the other groups, but the occurrence of interactions precludes an isolated groups analysis. We interpret the results within the framework of visual attention and discuss both, the implications of our results and the practical consequences.